2020
DOI: 10.4103/jfmpc.jfmpc_413_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of oral health and treatment necessities in hemophilia individuals of Davangere population — A case control study

Abstract: Background: The integrated approach towards the oral care of individuals with special needs requires proper motivation and prophylactic guidance by primary health care professionals, including musculoskeletal support to psychological therapy. In developing countries like India, oral care is not of primary importance as oral hygiene practices are less performed by compromised individuals suffering from hemophilia. Here, primary health care professionals play a significant role. The present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…These results differ from the study in Bulgaria, as in the Balkans there are clear similarities between the groups in practicing this habit [ 14 , 20 ]. Other researchers have shown that oral hygiene practices were similar between a hemophilia group and control group [ 11 , 17 , 18 ]; most children performed oral hygeine habits twice per day, and there was no significant difference in oral hygiene practices between the groups. It is due to the interdisciplinary approach in Western European countries, where dentists have been an essential part of the treating team of people with hemophilia for decades [ 17 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results differ from the study in Bulgaria, as in the Balkans there are clear similarities between the groups in practicing this habit [ 14 , 20 ]. Other researchers have shown that oral hygiene practices were similar between a hemophilia group and control group [ 11 , 17 , 18 ]; most children performed oral hygeine habits twice per day, and there was no significant difference in oral hygiene practices between the groups. It is due to the interdisciplinary approach in Western European countries, where dentists have been an essential part of the treating team of people with hemophilia for decades [ 17 ].…”
Section: Discussionmentioning
confidence: 80%
“…Controversy exists about whether there is better oral health in the deciduous dentition of children with hemophilia or in control groups because patients with hemophilia tend to be from families with lower social status, which is a well-known determinant of higher cariogenicity, especially in young children [ 8 , 10 ]. However, differences in oral status decrease and even become insignificant when comparing groups of adults [ 11 ]. Because dental caries and periodontitis are diseases in which health determinants accumulate over time, such as various bacteria and poor oral hygiene techniques, in order to clarify the differences in oral status in children and adults, future prospective studies with larger study groups are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was employed in previous studies to compare the HRQoL of the patients with the general population. 24,25 Descriptive statistics, including the mean, standard deviation (SD), number and proportion (%), were computed for demographic and clinical variables for respondents. Differences in proportions for categorical variables were evaluated by Chi-square test for age, marital status, education, occupation, income, history of smoking and drinking, chronic diseases combination and Fisher's exact test for ethnicity and health insurance type.…”
Section: Discussionmentioning
confidence: 99%
“…The 1:1 case‐controlled match was conducted among the PwH (hereafter ‘patient group’) and the general population (hereafter ‘general group’) based on gender and age. This approach was employed in previous studies to compare the HRQoL of the patients with the general population 24,25 . Descriptive statistics, including the mean, standard deviation (SD), number and proportion (%), were computed for demographic and clinical variables for respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Studies comparing the oral health status in children, adolescents and adults PWH with aged‐matched healthy controls reported contradicting outcomes. These studies reported that PWH might have a better, similar or worse dental condition compared to the healthy controls 8–22 . Despite these contradicting outcomes, more recent studies found no difference in Oral Health‐Related Quality of Life (OHR‐QoL) between children and adolescents PWH and healthy controls 13,17,21 .…”
Section: Introductionmentioning
confidence: 99%